STUDI HISTOLOGI PANKREAS TIKUS PUTIH (Rattus norvegicus L.) SETELAH PEMBERIAN CUKA DARI KULIT NANAS (Ananas comosus L. Merr) - Christin Monica Hermawati; Agung Janika Sitasiwi; Siti Nur Jannah (Jurnal Pro-Life, 2020)
Diabetes mellitus is a metabolic disease that occurs due to impaired insulin secretion caused by progressivedestruction of beta cells. Pineapple peel vinegar containing acetic acid and antioxidants has the potential to helpimprove the structure of beta cells in the Langerhans islet. This study aims to examine the effectiveness of pineapplepeel vinegar towards the histological improvement of Langerhans islet in diabetic rats. Twenty-four rats weredivided into 6 groups, normal control, positive control (diabetes + 0,4 ml apple vinegar), negative control(diabetes + water), test groups dose I, II, and III (0,2 ml; 0,4 ml; 0,8 ml pineapple vinegar). The treatment groupthat given 0.4 ml pineapple peel vinegar showed improvement in islet's structure as indicated by its size andnumber that close to normal. The results of the statistical analysis using Kruskal-Wallis followed by Mann-Whitneyshowed that the diameter of the Langerhans islet in group P2 (treated by 0,4 ml pineapple peel vinegar) was closeto normal. The improved structure of the Langerhans islet resulted in a decrease in blood sugar levels by 41,63%.This percentage is still lower than the K+ group (treated by 0,4 ml apple vinegar) by 52,89%. The antioxidantactivity in vinegar improves the structure of the Langerhans islet by binding to free radicals that cause damage.The acetic acid in vinegar inhibits disaccharidase activity so that it can control blood sugar levels.Keywords: Diabetes mellitus, alloxan, pineapple peel vinegar, antioxidants, acetic acid